PENGGUNAAN APLIKASI KASIR DALAM MENDUKUNG DIGITALISASI TRANSAKSI DI WARMINDO BESTIE - Sanjaya, Lucky; Yusuf, Naufal Ihsanul Fajrin; Izdihar, Rafi Dhia; As Syahril, Subhandika Prima; Hidayah , Yasha (POLITEKNIK LP3I JAKARTA, 2025)
A cashier application helps SMEs improve transaction efficiency and accuracy. With a digital system, payment processes become faster and reduce the risk of miscalculations. Additionally, this application makes it easier for business owners to manage financial data, allowing them to monitor income and expenses more accurately. Customers also benefit, as transactions become more transparent and convenient. This study involved interviews with business owners and customer surveys, which showed that using a cashier application positively impacts business operations. To maintain a competitive edge, it is essential to enhance data security and provide ongoing technical support. With the right technology, SMEs like Warmindo Bestie can grow faster and offer better services to their customers.